Venlafaxine versus amitriptyline in the prophylactic treatment of migraine: randomized, double-blind, crossover study - Bulut, S; Berilgen, MS; Baran, A; Tekatas, A; Atmaca, M; Mungen, B (Elsevier Science Bv, 2004)
In patients with migraine with or without aura the prophylactic effect of amitriptyline (AMT) and venlafaxine (VLF) was compared in a randomized double-blind crossover study. Intolerable side effects resulted in drop out of five patients on AMT (due to hypersomnia, difficulty in concentration and orthostatic hypotension) and one patient on VLF (because of nausea and vomiting). Following the run-in period the patients (n = 52) were randomly treated with one of the study medications for 12 weeks. After a wash-out period lasting 4 weeks the patients were treated with the other drug for further 12 weeks. Both drugs had significant beneficial effect on pain parameters. Total number of side effects of VLF was low when compared with the side effect profile of AMT. In conclusion, it is suggested that VLF may be considered for the prophylaxis of migraine because of its low and/or tolerable side effect properties. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: migraine; prophylaxis; amitriptyline; venlafaxine